Potentials of ultra-short-pulse time-domain scattering measurements. - van Cappellen, W.A (IEEE Antennas & propagation magazine.)
This article illustrates the potentials of ultra-short-pulse time-domain scattering measurements, and describes a facility to perform such measurements. The main advantages of measuring in the time domain are the high range resolution and the relatively simple measurement setup. A time-domain radar cross section measurement of a flat plate is performed, to illustrate the advantages of such methods over a conventional frequency-domain setup. The measurement was performed with a sampling oscilloscope, a pulse generator, and two 2-12 GHz ridged-horn antennas. Because the horns were not designed for transmitting transient signals, an additional system-response measurement, in combination with a software deconvolution algorithm, restored the impulse response of the object under test. Further processing separated the response of the object from clutter. A comparison of the time-domain data with calculated and measured frequency-domain radar cross sections shows good agreement. The high range resolution (100 ps) enabled the separation of scattering mechanisms (i.e., reflection, single and multiple diffraction). It is concluded that ultra-short-pulse time-domain measurements could be very beneficial.